Generative AI Robs Students of the Joy of Learning - Ian Fellows (GiLE Journal of Skills Development)
Rapid developments in the field of Generative AI have caused businesses, educators and politicians to consider how best to accommodate and utilise these new technologies. This article explores the implications of using AI, particularly Large Language Models (LLMs), in the writing process. While accepting that artificial intelligence has many valid and valuable uses in other spheres of human existence, this article argues that using LLMs at any stage of the academic writing process beyond grammar-checking is detrimental to student learning. This article explains the importance of students mastering each stage of the Basic Model of Learning to Write Well (learning, thinking, writing), identifies higher-order thinking as the key objective of education and reminds readers of why learning is one of the most joyful activities a human can experience.